Pemanfaatan Media Canva untuk Membuat Label Kemasan dalam Meningkatkan Kemampuan Mendesain pada Pembelajaran Produk Kreatif dan Kewirausahaan pada Siswa Kelas XI SMKS Perikanan dan Kelautan Jember - Rahayu, Putri Pinasti (ISLAMIKA, 2024)
This research is a qualitative study, which involves observing people and behaviors that can be observed using spoken or written words to produce relevant descriptive data. The success indicators in this research are the improvement of Designing abilities in Creative Product and Entrepreneurship Learning for 11th-grade students at the Fisheries and Marine Vocational High School (SMKS) in Jember. The objectives of this research are: 1) To determine the utilization of Canva media in creating Packaging Labels to enhance designing skills in creative product and entrepreneurship learning for 11th-grade students at SMKS Fisheries and Marine in Jember. 2) To ascertain the enhancement of Packaging Label designing skills using Canva media in creative product and entrepreneurship learning for 11th-grade students at SMKS Fisheries and Marine in Jember. The respondents of this study are 13 11th-grade students from the Fisheries and Marine Vocational High School (SMKS) in Jember, comprising 8 males and 5 females. Data collection procedures involve steps taken by the researcher to obtain data in efforts to address the research problem. Specific techniques are required in data collection to ensure that the expected data are gathered and are truly relevant to the issues being addressed. The data collection procedures in this research include observation, interviews, and documentation. The qualitative research conducted at SMKS Fisheries and Marine in Jember yields the following conclusions: 1. Implementation of learning using Canva media for creating Packaging Labels can enhance designing skills in creative product and entrepreneurship learning for 11th-grade students at SMKS Fisheries and Marine in Jember. 2. The effectiveness of designing Packaging Labels with Canva Media is evident in that: a) it enhances designing skills and saves time, b) it boosts students' learning motivation by presenting related images and videos, c) Canva Media can be used for creating other media besides packaging label designs, enabling students to develop their skills in creating new things with Canva's assistance, d) with Canva Media, learning can enhance designing skills and save time, allowing students to creatively design products more effectively both inside and outside the classroom.